Prevalence and Predictors of Pressure Injuries From Spine Surgery in the Prone Position: Do Body Morphological Changes During Deformity Correction Increase the Risks?. Issue 22 (15th November 2017) - Lin, Shuxun; Hey, Hwee Weng Dennis; Lau, Eugene Tze Chun; Tan, Kimberly-Anne; Thambiah, Joseph Shantakumar; Lau, Leok-Lim; Kumar, Naresh; Liu, Ka-Po Gabriel; Wong, Hee-Kit
Abstract : Study Design: Review of data and prospective study. Objective: To investigate the prevalence and predictive factors of pressure injuries in spine surgery performed in the prone position, and to determine whether morphological changes and truncal shifts occurring during deformity correction predispose to this complication. Summary of Background Data: Spine surgery performed in the prone position presents the risk of developing pressure injuries. This risk is potentially increased in deformity correction, because it tends to involve more extensive procedures, with associated longer operating times. Methods: Cases of pressure injuries after spine surgery in the prone position were reviewed to ascertain prevalence and determine risk factors. Data including patient factors (age, sex, height, weight, body mass index, American Society of Anesthesiologists grade, comorbidities, Braden scale, neurological status, spinal pathology) and surgical factors (approach, procedure type, number of screws, operated levels, operative time) were collected. Independent risk factors were identified via multivariate analysis. A subsequent prospective analysis of all patients undergoing spinal deformity correction was conducted by performing intraoperative measurements of body morphological changes and shifts in truncal positions. Statistical correlation was performed to determine whether positional shifts cause pressure injuries. Results: The prevalence of pressure injuries was 23.0%. Previous skin problems ( P = 0.034), myelopathy ( P = 0.013), operative time >300 minutes ( P = 0.005), and more than four operated levels ( P = 0.006) were independent predictors of pressure injuries. Being a spinal deformity patient was also an independent risk factor for developing pressure injuries (odds ratio 3.31, P = 0.010). Significant changes in body measurements during deformity correction were predictive of pressure injuries. Conclusion: Pressure injuries are prevalent in patients undergoing spine surgery while prone. Future studies should investigate strategies to prevent this complication based on the multiple risk factors identified in the present study. Patients undergoing spinal deformity correction surgery are particularly at risk due to intraoperative body morphological changes. Improved padding methods should be trialed in future studies. Level of Evidence: 3